Pharmacokinetics of intramuscular morphine in the horse - Devine, Elizabeth P (Kansas State University, 2012)
Pharmacokinetics of Intramuscular Morphine in the Horse Elizabeth Devine, DVM; Butch KuKanich, DVM, PhD, DACVCP; Warren Beard, DVM, MS, DACVS Objective - To determine the pharmacokinetics of morphine after intramuscular administration in a clinical population of horses Design – Prospective, clinical study Animals – Pilot study included 2 normal horses and the clinical study included 75 horses Procedures – Morphine was administered at 0.1mg/kg, IM and 2-3 blood samples were obtained from each horse at various times from 0-9 hours after administration. Plasma morphine concentrations were measured using liquid chromatography and mass spectrometry. Results – Data was analyzed using a naïve pooled pharmacokinetic model. The half-life for the elimination phase was approximately 1.5 hours, the volume of distribution (per bioavailability) was approximately 4.5 L/kg and the clearance (per bioavailability) was approximately 35 mL/kg/min. The peak plasma concentration was 21.6 ng/mL and occurred approximately 4 minutes after administration. Plasma concentrations of morphine were below the limit of quantification by 7 hours in 74 horses. Conclusions and Clinical Relevance – The relatively short half-life of morphine indicates the need for frequent dosing to maintain targeted plasma concentrations. Adverse effects were uncommon in this study and morphine was well tolerated at a dose of 0.1 mg/kg, IM. Morphine may be a useful adjunctive therapy in painful horses, but the variable plasma concentrations suggest the dose and dosing interval may need to be adjusted to the individual patient’s response.
Keywords: Morphine; Pharmacokinetics; Equine; Veterinary Medicine (0778)